Evaluation of the effectiveness of RESAN vaccine in the prophylaxis and treatment of endometriosis – an experimental study in an animal model. Part I - Szymanowski, Krzysztof; Chmaj-Wierzchowska, Karolina; Niepsuj, Joanna; Yanchanka, Andrey; Florek, Ewa; Barlik, Magdalena; Opala, Tomasz (Menopause Review/Przegląd Menopauzalny, 2007)
Endometriosis is a serious social problem. There is no fully effective form of treatment of endometriosis. Immunomodulation might be a chance to improve the results. Objectives: The aim of our study was to evaluate the effectiveness of the RESAN vaccine in the prevention and treatment of endometriosis in an experimental animal study. Materials and methods: A group of 58 sexually mature female rats was divided into three smaller groups. During the first step of the experiment RESAN vaccine was injected in group I of rats (n=24). Three months later during the 2nd step of the examination endometriosis was implanted in groups I and II (n=24). Group III (n=10) was a control group where sham operations were performed. Three months later endometrial implants were removed and examined histologically. Meanwhile RESAN vaccine was injected as a treatment in group II (step 3). Three months later an excision of the suspected foci was performed with histological examination of the tissue samples (step 4). Results: During step 3, the endometriosis was histologically diagnosed in 1 rat from group I and in 16 from group II. Adhesions near the endometrial implant were found in 3 and 14 rats from groups I and II, respectively. There were no endometriotic foci in all groups during the 4th step of the examination. Conclusions: 1. RESAN vaccine is an effective form of endometriosis prevention in a rat model. 2. Immunotherapy connected with surgical treatment is an effective form of treatment in an animal model of endometriosis.